Detection of Salmonella Bacteria In Soybean Tempeh Produced In Palekko Village, Takalar Regency - Anggraeni, Nur Afni; Naid, Tadjuddin; Nuryanti, Siska (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Tempeh is a staple food in Indonesia, known for its nutritional benefits, including 25% protein, 5% fat, 4% carbohydrates, vitamin B12, and rich mineral content. Ensuring the safety and hygiene of tempeh is crucial, especially in preventing contamination by harmful bacteria like Salmonella, which poses serious health risks. This study aimed to detect the presence of Salmonella bacteria in tempeh produced in Palekko Village, Takalar Regency, using Salmonella Shigella Agar (SSA) medium. The method employed was experimental, involving the preparation and dilution of tempeh samples followed by incubation on SSA medium. The results is a no samples detected Salmonella met the Salmonella contamination limit requirements, which were negative/25g.